Pruritic papular rash as a prodromal manifestation of COVID-19 - Rand Almuhyi (Termedia Publishing House, 2022)
The spectrum of clinical manifestations of coronavirus is very wide and can affect different organ systems including the skin, hence the cutaneous manifestations associated with coronavirus infection are an important issue to consider. Here, we present a patient with pruritic papular rash resolved leaving behind hyperpigmentation as the first manifestation of coronavirus infection.